The current state of Clinical Mycology in Eastern and South-Eastern Europe. (23rd February 2022) - Driemeyer, Cândida; Falci, Diego R; Hoenigl, Martin; Cornely, Oliver A; Chakrabarti, Arunaloke; Gangneux, Jean Pierre; Segal, Esther; Jürna-Ellam, Marika; Matos, Tadeja; Meis, Jacques F; Perfect, John R; Arsenijevic, Valentina Arsic; et al.
Abstract: The ability of medical centers in Eastern and South-Eastern Europe to diagnose and treat fungal infections remains unknown. In order to investigate that, here we conducted a cross-sectional online survey, released at both The International Society for Human & Animal Mycology (ISHAM) and European Confederation of Medical Mycology (ECMM) websites. A total of 31 institutions responded to the questionnaire. Most centers (87.1%, n = 27) had access to Aspergillus spp. ELISA galactomannan testing as well as to Cryptococcus spp. antigen testing (83.9%, n = 26). Serological tests were mostly available for Aspergillus species (80.6%, n = 25); and most institutions reported access to mold-active antifungal drugs (83.9%; n = 26), but 5-flucytosine was available to only 29% (n = 9) of the participant centers. In conclusion, this study represents the first attempt to document the strengths and limitations of the Eastern and South-Eastern European region for diagnosing and treating fungal diseases. Lay Summary: Our article is about the availability of diagnostic and treatments tools related to fungal infections in the countries of Eastern and South-Eastern region. Surveys like these are important to understand the gaps and point towards the fungal infections as a global health issue.